All-Intra-articular Arthroscopic Rotator Cuff Repair - Pablo Ruben Rupenian, M.D. (Arthroscopy Techniques, 2017)
This Technical Note presents an arthroscopic technique to repair rotator cuff tears using a constant intra-articular (glenohumeral) portal for visualization. The smoothness of both the humeral head cartilage and the articular side of the rotator cuff offers a cleaner arthroscopic approach, while the absence of a subacromial bursa also reduces bleeding, turbidity, and the need for iterative soft tissue debridement. It also facilitates the recognition and repair of certain tear patterns. The intra-articular perspective allows the surgeon to visualize how stitches pierce the tissue in a desired and resistant area of the tendon. During knot tying, instead of watching the knot compressing against the bursal side of the tendon, the surgeon monitors how the articular side of the tendon is compressed and attached against the footprint while pushing the knot until the desired level of reduction is achieved.